Asymmetric multilevel topology for photovoltaic energy injection to microgrids - Munoz, Javier; Gaisse, Patricio; Baier, Carlos; Rivera, Marco; Gregor, Raul; Zanchetta, Pericle (2016)
The massive penetration of renewable energy sources in the utility grid has emerged as the solution to obtain clean energy in modern electric systems, which are gradually replacing their generators that produce CO2 emissions to achieve a sustainable growing. Power electronics is quite relevant in the deep penetration of renewable energy, because the use of such equipment is mandatory to integrate these new resources with the existing facilities. In order to reach higher power ranges, multilevel topologies are the state-of-the-art solution, due to the limited rating of the actual semiconductor devices. Furthermore, latest trends show that asymmetric multilevel configurations are an attractive technology to connect directly the power converters to the grid. This paper analyze the photovoltaic energy injection to microgrids using a hybrid approach that mixes the existing topologies: string, multistring and central inverter to implement an asymmetric structure that generate highly sinusoidal resulting waveforms. This document includes a simple analysis of the proposed configuration and highlights the advantages of using an asymmetric converter, supported with stationary and dynamic simulated results.